A Heuristic for Integrating Sense of Place Into Ocean Governance - Joe Duggan; Christopher Cvitanovic; Ingrid van Putten; Sarah Clement (Ocean and Society)
Sense of place (SoP) is a powerful yet underutilised social value with significant potential to improve collaboration and inclusivity in ocean governance. Recent evidence, however, has shown that a range of barriers prevent the routine integration of SoP in this space. To help overcome this, this commentary proposes a preliminary heuristic—or rules of thumb—that can help guide researchers and practitioners to help them incorporate SoP into ocean governance. The heuristic emphasizes fostering collaboration, inclusivity, and shared understanding among diverse stakeholders and non‐academic actors. It advocates for the co‐production of knowledge across disciplines and institutions, iterative reflexivity to address positionality, and the creation of shared definitions and measures of SoP tailored to specific contexts. It explores balancing a broad conceptual understanding of SoP with localized tangible applications to ensure relevance and impact. Celebrating “bright spots,” or successful instances where research has informed policy, is also highlighted as a way to inspire and support the utilization of SoP in management decisions. By utilizing SoP as a relational tool, we posit that ocean governance practitioners can enhance trust, promote more meaningful stakeholder engagement, and align diverse perspectives toward common goals, thus building more inclusive and collaborative management practices.